(untitled) (Jahangirnagar University Journal of Biological Sciences, 2017)
Experiments were carried out in two consecutive cropping seasons to evaluate the effectiveness of seven insecticides against brinjal shoot and fruit borer (BSFB) in the experimental farm of the department of Entomology, BSMRAU, Bangladesh. Tracer-45 SC was found to be highly effective in reducing 88.22 % and 84.41 % shoot infestation over control during summer and winter, respectively followed by Proclaim-5 SG (74.12 % in summer and 64.36 % in winter). The highest number of healthy fruits per plant (22.38 in summer and 35.69 in winter, respectively) and the highest yield of eggplant per hectare (19.94 t/ha in summer and 24.79 t/ha in winter) were obtained from Tracer-45 SC treated plots. Therefore, it may be concluded that Tracer-45 SC (Spinosad) @ 0.4 ml/liter could be the most effective insecticide in controlling brinjal shoot and fruit borer and also in getting highest yield of eggplant. Jahangirnagar University J. Biol. Sci. 6(1): 35-43, 2017 (June)